PETROLOGÍA Y CRISTALIZACIÓN FRACCIONADA DE LOS BASALTOS – ANDESITAS BASALTICAS DE LA FORMACIÓN GUANEROS (LA YARADA – TACNA – PERÚ) - Malpica Sandoval y Cols., Carlosa (2019)
The racks concerní un the formation Guaneros exposed in The Yarada –Tacna – Peru (Fig. 1). Si determination two series volcanic the lower (samples Ly 6, 5, 1, a) and the upper (samples Ly 12, 14, c, b), constitutes for basalts and basaltic andesitic. The espectrum of earth rare of the basalts of the two series similar even the erbium, indication a trancition between the end of melting anfibole and begin of the melting garnet. The process fractionation cristallisation, partial melting, change chemical magma and the formation of the texture porfiritic.